T.MÁTMURATOV SHÍǴARMALARÍNDA QAYTALAW HÁM ONÍŃ TÚRLERI - Buxarbaeva, J. (SCIENCE and SOCIETY, 2021)
The article studied the artistic and methodological application of repeated words used in the works of the poet T. Matmuratov. Also on some types of phonetic, lexical, morphological and synthactic repeats are shown from fragments of the poet’s works.